Etnična diskriminacija na trgu delovne sile - Brezigar, Sara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2005)
The first part of the article brings a survey of different forms and evaluation methods of ethnic discrimination. The second part discusses three dilemmas concerning ethnic discrimination on the internal labour market. The first dilemma is about the paradox of discrimination. When taking decisions on education, training, financial stimulation and promotion of individual work organization members, employers and human resources managers are often faced with the "between a hammer and an anvil" situation. On the one hand they need methods of human resources selection, which are sufficiently discriminatory to enable them to find the most appropriate candidate for promotion, money bonus or expensive training, and on the other hand these methods could become means of indirect ethnic discrimination. The second dilemma concerns the elusive nature of ethnic discrimination. Inner labour market knows cases of subtle discrimination seriously threatening successfulness of ethnic minority members. Yet such cases are very hard to discover. Furthermore, there is a question of the deliberate nature of such treatment which is indeed very hard to prove. The third dilemma deals with the cumulative character of ethnic discrimination in organizations. This, too, is a kind of "between a hammer and an anvil" situation - should they strive to eliminate discrimination through the policy of positive discrimination, or should they - by insisting on the principle of equal treatment and opportunities - reproduce the cumulation of ethnic discrimination, an individual has suffered in other spheres of his life?
Keywords: delovna sila; treg delovne sile; etnična diskriminacija; zaposlovanje